2012
DOI: 10.2139/ssrn.2016850
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of Business Administration Literature in Google Scholar: Analysis and Comparison with Econbiz, Scopus and Web of Science

Abstract: Google Scholar is used for literature research as well as for evaluations of research performance. To establish Google Scholar's functional compliance, we generate a heuristic method and apply it to business relevant journals, namely those ascertained and rated in the German business journal ranking VHB-JOURQUAL2 by Schrader/Hennig-Thurau (2009). It is shown that Google Scholar primarily indexes international, i.e. English-language journals with a high rating grade; national language, here German-language lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…As stated in the introduction we expected the ACM Digital Library to have the best coverage, however this assumption was shown to be wrong, as Scopus had the highest number of publications, citations and average number of citations per paper. This is different from the finding for business administration, where the subject specific database had the best coverage (Clermont and Dyckhoff, 2012) based on journal titles. The major goal of this paper was to highlight the importance of coverage for comprehensive data retrieval.…”
Section: Discussioncontrasting
confidence: 94%
“…As stated in the introduction we expected the ACM Digital Library to have the best coverage, however this assumption was shown to be wrong, as Scopus had the highest number of publications, citations and average number of citations per paper. This is different from the finding for business administration, where the subject specific database had the best coverage (Clermont and Dyckhoff, 2012) based on journal titles. The major goal of this paper was to highlight the importance of coverage for comprehensive data retrieval.…”
Section: Discussioncontrasting
confidence: 94%
“…It is widely used for information retrieval, but its suitability for research evaluation and other bibliometric analyses has been highly questioned because of the sporadic coverage of non-English literature, various inconsistencies (e.g. indexation of non-existing journals) in the data (Clermont and Dyckhoff, 2012), and a lack of transparency of the coverage (Wouters and Costas, 2012). Furthermore, López-Cózar et al (2014) have shown that the citation data in Google Scholar can easily be manipulated by researchers who would want to increase their citations count.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the coverage of WoS, Scopus and Google Scholar to calculate h-index of a sample of authors, they conclude that more than one tool must be used in order to provide a thorough assessment of a researcher's impact. In the field of Business and Management, Mingers andLipitakis (2010), andClermont andDyckhoff (2012) showed that Google Scholar mainly indexes international, English-language journals and while it includes unreliable data, it has a better coverage compared to Scopus and WoS. Meho and Yang (2007) compared citation data and ranking of scholars in the field of Library and Information Science using WoS, Scopus and Google Scholar.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have investigated the journal coverage of WoS and Scopus based on field classifications, publisher countries and publication languages, reporting very general information (Gavel & Iselid, 2008;Archambault et al, 2009;Mongeon & Paul-Hus, 2016). Other studies have analysed coverage in specific areas, including: Social Sciences and Humanities (Archambault et al, 2006), Computer Sciences (Franceschet, 2009), Library and Information Science (Abrizah et al, 2012), Business Administration (Clermont & Dyckhoff, 2012) or Earth and Atmospheric Sciences (Barnett & Lascar, 2012). WoS and Scopus have also been compared for selected geographical areas: Latin American (Collazo-Reyes, 2014); Latin American and Caribbean (Santa & Herrero-Solana, 2010); Russia (Moed, Markusova & Akoev, 2018) and Norway (Aksnes & Sivertsen, 2019); and one study has combined a geographic area and subject: Spanish Psychology (Osca-Lluch et al, 2013).…”
Section: Introductionmentioning
confidence: 99%